(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2012)
In Philip Gourevitch’s 1998 tome on the Rwandan genocide he writes: “power largely consists in the ability to make others inhabit your story of their reality.” Placed upon the structurally violent backdrop of centuries of caste-based marginalization and injustice, such a statement has a familiar resonance for the oppressed of modern India. Such an understanding of power provides one important key to unlocking the nested intersectionality of caste-based forms of personal, cultural and structural violence. But to many dalits (ex-‘untouchables’) in India, breaking away from the powerful ‘caste Hindu’ story has required more than this understanding of power. For many dalits the creation of a new ‘narrative identity’ as socially engaged Ambedkar Buddhists has become the only path to liberation from caste oppression. While dalits’ creation of an Ambedkar Buddhist identity is, at least in part, an attempt to make others (especially ‘caste Hindus’) inhabit dalits’ own story of their reality, it is also a radical move towards self-awareness and awakening to a creative vision of social change which aims to foster a new self-image for victims of marginalization. This process of fostering “critical consciousness” is fraught with dialectic paradoxes, which attention to narrative structure can help clarify and demystify.